Asbabun Nuzul dalam Pandangan Ulama Klasik dan Kontemporer - Isyanto, Nur (STAINI Press, 2023)
Asbabun Nuzul refers to the reasons for the revelation of the verses of the Koran, which are important to understand in interpreting the holy text. This article reviews the meaning of this concept based on the views of classical and contemporary scholars, providing a deeper understanding of the interpretation of the Qur'an. Apart from that, this article discusses the urgency and function of Asbabun Nuzul in the context of interpreting the Al-Qur'an. Asbabun Nuzul helps in exploring the wisdom of legal law, specializing law, and ascertaining the meaning of Al-Qur'an verses, thus playing an important role in the application and interpretation of sacred texts for Muslims.